Climatic change impacts on Chinese sugarcane planting: Benefits and risks. (April 2020) - Liang, Yulian; Yu, Sufang; Zhen, Zhen; Zhao, Yinjun; Deng, Jianming; Jiang, Weiguo
Abstract: China is the world's third largest sugar consumer and fourth largest sugar producer, and approximately 90% of sugar comes from sugarcane in China. Understanding the influence of climate change on sugarcane planting patterns and their suitability is conducive to the strategic decisions related to future agricultural adaptation. In this study, based on climatic resources and climate hazard indexes, a new climatic suitability index of sugarcane (CSIS ) was established. A CSIS of the current climate period (1981–2010) was proposed for investigating the present planting pattern of sugarcane based on historical climate observations. We also projected the future changes in the CSIS and discussed the variation in the planting patterns of sugarcane in the middle of the 21st century (2020–2050) and the end of the 21st century (2071–2100) under the RCP4.5 scenario using projection data from the CMIP5. The regions with a CSIS >0.2 had influence on sugarcane planting. The results of the CSIS in the current climate period showed that sugarcane is distributed in areas with a CSIS ≥ 0.2, while areas with the highest sugarcane yield correspond to areas with a CSIS ≥ 0.6. The areas of sugarcane planting in China can be classified into three grades: plantable area (0.2 ≤ CSIS  < 0.4), suitable area (0.4 ≤ CSIS  < 0.6) and optimal area (CSIS  ≥ 0.6). In the middle 21st century, suitable sugarcane planting area grades showed an increase under the projection of the RCP4.5 scenario. The plantable area was extended to the south of Shandong Province and the north bank of the middle and lower reaches of the Yangtze River, mainly because the frost hazard was alleviated and the heat index increased. In addition to the increase in heat conditions, an increase in total solar radiation was also found to play a role in the expansion of suitable areas in Chongqing in western China. The optimal area covers southern China, Jiangxi and southern Hunan in central China and eastern Zhejiang in eastern China. By the end of the 21st century, this positive effect was further expanded, but for Hainan Province, due to intense heat accumulation and intensified drought, heat injury occurred; thus, emphasis of sugarcane planting in this area should be placed on disaster prevention. In central and southwestern China, the CSIS still has great potential to reach saturation so that more efforts should be implemented to expand the planting area and improve the yield quality and sugar content. Highlights: Climatic suitability index of sugarcane was established to evaluate the suitability for sugarcane planting. The risk of planting sugarcane in the southern China will increase due to intensive drought and heat events in future. The risk of planting sugarcane in the central China will be mitigated by less frosts and increased heat.